Rethinking Beijing's Geostrategic Sensibilities to Tibet and Xinjiang: Images and Interests1. (4th August 2013) - Seo, Jungmin; Cho, Young Chul
Abstract : The aim of this essay is to examine the ways in which Beijing perceives the issues of Tibet and Xinjiang differently in the context of its geostrategic thinking in international politics today. In doing so, this essay will provide a deeper understanding of Beijing's different geostrategic sensibilities of Tibet and Xinjiang in regard to rising China's national security interests in Central and South Asia. This essay argues that, although Beijing publicly sees the Tibet and Xinjiang problems as issues of securing Chinese sovereignty, geostrategically Beijing alludes to a subtle difference in its perception of the two regions: (i) the Tibet problem is a practical, domestic issue to be handled by Beijing's paternalistic engagement of modernization, and is a symbolic issue regarding how to manage rising China's benign image abroad while harshly oppressing any separatist voices in Tibet; and (ii) in Beijing's geostrategic thinking, Xinjiang's security importance seems to be defined in terms of energy security for China's economic growth, which is integral to social stability and the Chinese Communist Party's legitimacy, as well as the transnational Islamic terrorist movement interlinked with Uyghur separatism in Xinjiang.